Genetic Susceptibility to Coronavirus Disease 19 (COVID-19): A Review - Yahaya, Tajudeen; Oladele, Esther; Nnochiri, Kelechi; Abdullahi, Haliru; Nathaniel, Josephine (Translation: The University of Toledo Journal of Medical Sciences, 2021)
Background: Certain gene polymorphisms are suspected to contribute to the geographic-specific susceptibility of people to coronavirus disease 19 (COVID-19), which may be used as therapeutic targets. Accordingly, this review articulates suspected COVID-19 susceptibility genes to assist researchers and medical practitioners to formulate effective drug and treatment procedure. Method: Reputable electronic academic databases, including PubMed, Springer Link, and Scopus were searched for relevant information on the subject. Results and Discussion: The search identified seven COVID-19 susceptibility genes, which are TICAM2, TLRs, ACE, ABO blood group gene, HLA, and TMPRSS2. Polymorphisms in ACE and TMPRSS2 may increase or decrease the binding of the virus to the human cell, while polymorphisms in TICAM2, TLRs, and HLA may enhance or compromise the immune system. Type O blood group seems to be the most protective ABO blood group because of its abundant antibodies and blood clothing inhibition, while type A blood group is the least protective. The distribution of the polymorphisms is influenced by geographical locations, which could contribute to the worldwide differential vulnerability of people to the disease. Most protective polymorphisms are prevalent among Africans and Asians, which could be the reason for their less susceptible to the disease compared to Europeans and Americans. Most genes reside on the X - chromosome, which could partly explain the dominance of the severe form of the disease among men than women. Conclusion: Polymorphisms in certain genes may modulate COVID-19 infectivity and severity. A thorough understanding of the biological mechanisms of these genes may help design a cure.